Evaluation of Research Standards at Ministry of Research, Technology and Higher Education with I-MR Map Control Analysis - Muhammad Dimyati; Akhmad Fauzy (Universitas Ahmad Dahlan, 2018)
In order to accommodate research activities at all universities in Indonesia, the Directorate Genereal of Strengthening for Research and Development, Ministry of Research, Technology, and Higher Education (Kemenristekdikti) of the Republic of Indonesia established research quality standard. The standard includes the minimum targets that must be achieved by each University at the period of conducting the research activity. However, until now there has been no measurement to find out whether the existing standard was good enough or needs to be evaluated. Therefore, this study was conducted to measure the standards. The method used was the analysis of I-MR (Individual and Moving Range) control chart to see the performance of the standard. The results show that existing research schemes have encouraged the improvement of international publications, but have not yet maximized the production of other outputs such as textbooks, accredited national publications, intellectual property rights, and ptototypes. The result of the research was expected to be used as material for evaluation and improvement of policy to improve the quality of research standard in Kemenristekdikti.